(untitled) (International Conference on Computers in Education, 2013)
Many students have difficulty in translating from English to Chinese and Chinese to English, particularly long and complicated sentences, and errors in their organizing information often result in wrong interpretation of the intended meaning in the context. Few papers offer a comprehensive guide to teaching translation in practice, especially embedding technology into a translation class rather than simply searching for vocabulary items online. The study explores the effectiveness of online collaborative translation activity. The instruments used included a pretest, a posttest, and a UTAUT survey. The results are discussed in terms of the effectiveness of the online translation tasks and suggestions are provided for future task design.